Recognition Through Prior Learning: Reducing ‘Mis-recognition’ of International Students in UK Higher Education (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Prior learning of international students is significantly undervalued in UK Higher Education (HE).  This conceptual paper utilises Axel Honneth’s theory of social justice as ‘recognition’ as a lens to examine how ‘recognition of prior learning’ (RPL) can be extended beyond accreditation purposes in UK HE into pedagogical and teaching spaces.  An outline of Honneth’s theory is provided and used to examine existing circumstances of mis-recognition facing international students. This paper then identifies and builds on existing RPL and international student literature to make the case that concepts of ‘recognition of prior learning’ can be extended to facilitate ‘recognition through prior learning’ and thus address issues of mis-recognition faced by international students.Key Words: International Students; Recognition; Prior Learning; Honneth